The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia - Cipola, Nikolas Gioia; Morais, José Wellington De; Bellini, Bruno Cavalcante (Zootaxa, 2017)
Herein four new species of Lepidocyrtoides are described and illustrated: three from Brazilian Amazon, L. caeruleomaculatus sp. nov., L. colormutatus sp. nov. and L. bicolorangelus sp. nov., all similar to each other by macrochaetotaxy reduced; and L. hopkini sp. nov. from New South Wales, Australia. Lepidocyrtoides tapuia comb. nov. (Arlé & Guimarães) and L. villasboasi comb. nov. (Arlé & Guimarães) are redescribed and transferred from Lepidosira Schött due to projection of mesothorax over head and manubrial plate with blunt macrochaetae. Neotypes are designated to both species. The holotype of L. oliveri Liu, Chen & Greenslade is analyzed and details of the dorsal chaetotaxy are added. Keys to the five species of the genus from Brazil and six from Australia are provided. Lepidocyrtoides now is recorded from the New World, South and Southeast Asia and Oceania, and the records of Lepidosira in the American continent are excluded.